China's top 10 hematological advances in 2021 lists the key developments in hematology in China for that year. Issue 1 (25th January 2022) - Wang, Xiaochen
Abstract : Abstract: The China's top 10 hematological advances in 2021 was announced at the 2 nd Annual Meeting of Chinese Alliance for Societies of Hematology on January 16, 2022.